Soft technology implementation in Malaysian manufacturing companies at electrical and electronic industry. - Hami, Norsiah (Universiti Utara Malaysia, 2008)
Purpose – This research aims to report the findings of survey on soft technology implementation in Malaysian manufacturing companies of electrical and electronic industries.The objective of the survey is to identify the type of single soft technologies implemented, identify the level of performance attained by the implementers, and investigate differences in the level of performance attained with the numbers of single soft technologies implemented.Design/methodology/approach – responses from 64 companies are analyzed and presented.Findings – It is observed that most of Malaysian electrical and electronic companies are implementing TQM and MRP while CAPP is the least.Implementation of soft technology has sparked positive changes in all performance variables listed except reduce number of employees.The study also revealed that there was a not significant difference in the number of single soft technologies implemented in attaining the level of performance.Originality/value – This research report is useful to others implementing soft technology.